Pendampingan Penggunaan Kosakata Bahasa Inggris Menggunakan Media Pembelajaran Poster Pada Siswa SD N.100110 Siuhom - Fitri Rahma Handayani; Hidayanti Rohimah Nurdin (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
ABSTRACT Assistance in the use of Basic English Vocabulary in the village is one of the community service programs. The purpose of English learning assistance was to introduce to children of basic English material and able to pronounce basic words in English. The activities carried out during the training were the presentation of basic English material using poster learning media. Posters are learning media consisting of colors, pictures, graphics and writing to explain and express a concept, idea or message related to science. The location of Community Service on English tutoring for SD N.100110 in Siuhom Village, West Angkola Subdistrict, South Tapanuli District. The method of implementing Community Service regarding English tutoring for elementary school children is to use poster learning media. The results of the community service activities showed that the children were very excited and interested in the English learning assistance program and they could pronounce the English vocabularies well. Thus, assistance in the use of English vocabulary for elementary students can increase their knowledge of English. Keywords: Assistance, English, Posters